Sex-based differences in social trade-offs in a wild bird society - George H.T. Rabin; Adelaide D. Abraham; Taylor Bi; Keith McMahon; Ben C. Sheldon; Josh A. Firth (Animal Behaviour, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Sector expert and public perceptions of greening of grey infrastructure: a case study in Britain’s Ocean City - Jessica R. Allen; Anaëlle J. Lemasson; Melanie J. Bishop; Katherine A. Dafforn; Kate C. Dodds; Mick E. Hanley; Antony M. Knights; Mariana Mayer-Pinto; Abigail McQuatters-Gollop; Maria L. Vozzo; Louise B. Firth (Urban Ecosystems, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Evaluating the effects of probiotic supplementation and structural enrichment prior to transportation on the stress physiology of reintroduced juvenile Atlantic salmon - D. Roberts; C. L. Madliger; A. I. Mokdad; B. L. Firth; T. E. Pitcher (Environmental Biology of Fishes, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Could rear-arc volcanism be driven by mantle instability? - Alex C. Davidson; Chris W. Firth; Simon P. Turner; Shane J. Cronin (Chemical Geology, 2025)

Different types of social links contrastingly shape reproductive traits in a multi-level society of wild songbirds - Samin Gokcekus; Josh A. Firth; Ella F. Cole; Ben C. Sheldon; Gregory F. Albery (Behavioral Ecology and Sociobiology, 2025)
Social environments can influence individuals’ health, reproductive success, welfare, and survival. These environments consist of diverse social connection types at multiple levels, which could influence different components of fitness in contrasting ways. Great tits ( Parus major ) exhibit a multilevel society with four major types of dyadic bonds: pair mates, breeding neighbours, flockmates, and spatial associates, all of which can influence fitness. Here, we show that these different types of dyadic bonds are differentially linked with reproductive success metrics in a wild great tit population, and that the consideration of spatial effects could provide further insights into these interrelationships. Specifically, more-social individuals had more fledglings, those that bonded more strongly with their pairmate laid earlier, and those with more spatial associates laid smaller clutches. These findings highlight the importance of considering multiple types of dyadic relationships when identifying the fitness consequences of sociality, and the need for work to experimentally test these relationships, particularly in spatially structured populations.

Continent‐Wide Drivers of Spatial Synchrony in Breeding Demographic Structure Across Wild Great Tit Populations - Joe P. Woodman; Stefan J. G. Vriend; Frank Adriaensen; Elena Álvarez; Alexander Artemyev; Emilio Barba; Malcolm D. Burgess; Samuel P. Caro; Laure Cauchard; Anne Charmantier; Ella F. Cole; Niels Dingemanse; et al. (Ecology Letters, 2025)
Variation in age structure influences population dynamics, yet we have limited understanding of the spatial scale at which its fluctuations are synchronised between populations. Using 32 great tit populations, spanning 4° W–33° E and 35°–65° N involving > 130,000 birds across 67 years, we quantify spatial synchrony in breeding demographic structure (subadult vs. adult breeders) and its drivers. We show that larger clutch sizes, colder winters, and larger beech crops lead to younger populations. We report distance‐dependent synchrony of demographic structure, maintained at approximately 650 km. Despite covariation with demographic structure, we do not find evidence for environmental variables influencing the scale of synchrony, except for beech masting. We suggest that local ecological and density‐dependent dynamics impact how environmental variation interacts with demographic structure, influencing estimates of the environment's effect on synchrony. Our analyses demonstrate the operation of synchrony in demographic structure over large scales, with implications for age‐dependent demography in populations.

A novel class of insecticidal alkylsulfones are potent inhibitors of vesicular acetylcholine transport - James Goodchild; Ying-Ju Chen; Judith Blythe; Lucy C. Firth; Elizabeth Hirst; Kirsty Bess; Julia Bristow; Jenny Willis; Richard Baines; Francesca Cash; Michel Muehlebach; Anke Buchholz; et al. (Pesticide Biochemistry and Physiology, 2024)

Experimental manipulation of population density in a wild bird alters social structure but not patch discovery rate - Kristina B. Beck; Charlotte E. Regan; Keith McMahon; Sam Crofts; Ella F. Cole; Josh A. Firth; Ben C. Sheldon (Animal Behaviour, 2024)

Magnetic resonance imaging shows spinal curvature in Chinook salmon ( Oncorhynchus tshawytscha ) is associated with chronic inflammation of peri‐vertebral soft tissues - Bailey A. Lovett; Elwyn C. Firth; Matthew R. Perrott; John S. Munday; Beau P. Pontre; Anna‐Maria P. Lydon; Jane E. Symonds; Mark A. Preece; Neill A. Herbert (Journal of Fish Diseases, 2024)
Chinook salmon ( Oncorhynchus tshawytscha ) farmed in New Zealand are known to develop abnormal spinal curvature late in seawater production. Its cause is presently unknown, but there is evidence to suggest a neuromuscular pathology. Using magnetic resonance imaging (MRI), we evaluated the relationship between soft tissue pathology and spinal curvature in farmed Chinook salmon. Regions of interest (ROIs) presenting as pathologic MRI signal hyper‐intensity were identified from scans of 24 harvest‐sized individuals: 13 with radiographically‐detectable spinal curvature and 11 without. ROIs were excised from individuals using anatomical landmarks as reference points and histologically analysed. Pathologic MRI signal was observed more frequently in individuals with radiographic curvature (92%, n = 12) than those without (18%, n = 2), was localized to the peri‐vertebral connective tissues and musculature, and presented as three forms: inflammation, fibrosis, or both. These pathologies are consistent with a chronic inflammatory process, such as that observed during recovery from a soft tissue injury, and suggest spinal curvature in farmed Chinook salmon may be associated with damage to and/or compromised integrity of the peri‐vertebral soft tissues. Future research to ascertain the contributing factors is required.

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Synthesis and insecticidal activity of N-(5-phenylpyrazin-2-yl)-benzamide derivatives: Elucidation of mode of action on chitin biosynthesis through symptomology and genetic studies - Carmela Napolitano; Fides Benfatti; Farhan Bou Hamdan; Julia A. Bristow; Federico Dapiaggi; Lucy C. Firth; Marcus Guest; Helena A. Saunders; Roger G. Hall; Mattia R. Monaco; Vincent Quetglas; Stefano Rendine; et al. (Pesticide Biochemistry and Physiology, 2024)

Metrics matter: Multiple diversity metrics at different spatial scales are needed to understand species diversity in urban environments - Kathryn A. O'Shaughnessy; Antony M. Knights; Stephen J. Hawkins; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Louise B. Firth (Science of The Total Environment, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Drivers of passive leadership in wild songbirds: species-level differences and spatio-temporally dependent intraspecific effects - Samin Gokcekus; Josh A. Firth; Charlotte Regan; Ella F. Cole; Koosje P. Lamers; Ben C. Sheldon (Behavioral Ecology and Sociobiology, 2021)
Collective behaviors are typical for many social species and can have fitness benefits for participating individuals. To maximize the benefits obtained from group living, individuals must coordinate their behaviors to some extent. What are the mechanisms that make certain individuals more likely to initiate collective behaviors, for example, by taking a risk to initially access a resource (i.e., to act as “leaders”)? Here, we examine leading behavior in a natural population of great tits and blue tits. We use automated feeding stations to monitor the feeder visits of tagged individuals within mixed-species flocks, with a small cost (waiting Significance statement Many species are social and engage in collective behaviors. To benefit from group actions, individuals need to fulfill different roles. Here, we examine leading behavior during feeding events; who feeds first when birds arrive at a resource? In mixed-species flocks of passerines, great tits (the larger and more dominant species), males, and individuals with higher levels of activity lead more often than blue tits, females, and individuals with lower levels of activity. While the species effect remains even when we control for the locations and dates of individual feeder visits, the effects of sex and activity are dependent on when and where birds choose to feed.

Nitrogen removal in constructed marshes at sites protected from and exposed to waves - Nigel A. Temple; Eric L. Sparks; Just Cebrian; Sara E. Martin; Daniel C. Firth (Wetlands Ecology and Management, 2021)

Subzero, saline incubations of Colwellia psychrerythraea reveal strategies and biomarkers for sustained life in extreme icy environments - Miranda C. Mudge; Brook L. Nunn; Erin Firth; Marcela Ewert; Kianna Hales; William E. Fondrie; William S. Noble; Jonathan Toner; Bonnie Light; Karen A. Junge (Environmental Microbiology, 2021)
Summary Colwellia psychrerythraea is a marine psychrophilic bacterium known for its remarkable ability to maintain activity during long‐term exposure to extreme subzero temperatures and correspondingly high salinities in sea ice. These microorganisms must have adaptations to both high salinity and low temperature to survive, be metabolically active, or grow in the ice. Here, we report on an experimental design that allowed us to monitor culturability, cell abundance, activity and proteomic signatures of C. psychrerythraea strain 34H ( Cp 34H) in subzero brines and supercooled sea water through long‐term incubations under eight conditions with varying subzero temperatures, salinities and nutrient additions. Shotgun proteomics found novel metabolic strategies used to maintain culturability in response to each independent experimental variable, particularly in pathways regulating carbon, nitrogen and fatty acid metabolism. Statistical analysis of abundances of proteins uniquely identified in isolated conditions provide metabolism‐specific protein biosignatures indicative of growth or survival in either increased salinity, decreased temperature, or nutrient limitation. Additionally, to aid in the search for extant life on other icy worlds, analysis of detected short peptides in −10°C incubations after 4 months identified over 500 potential biosignatures that could indicate the presence of terrestrial‐like cold‐active or halophilic metabolisms on other icy worlds.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Social carry‐over effects underpin trans‐seasonally linked structure in a wild bird population - Josh A. Firth; Ben C. Sheldon (Ecology Letters, 2016)
Spatial structure underpins numerous population processes by determining the environment individuals' experience and which other individuals they encounter. Yet, how the social landscape influences individuals' spatial decisions remains largely unexplored. Wild great tits ( Parus major ) form freely moving winter flocks, but choose a single location to establish a breeding territory over the spring. We demonstrate that individuals' winter social associations carry‐over into their subsequent spatial decisions, as individuals breed nearer to those they were most associated with during winter. Further, they also form territory boundaries with their closest winter associates, irrespective of breeding distance. These findings were consistent across years, and among all demographic classes, suggesting that such social carry‐over effects may be general. Thus, prior social structure can shape the spatial proximity, and fine‐scale arrangement, of breeding individuals. In this way, social networks can influence a wide range of processes linked to individuals' breeding locations, including other social interactions themselves.

Inferring social structure from temporal data - Ioannis Psorakis; Bernhard Voelkl; Colin J. Garroway; Reinder Radersma; Lucy M. Aplin; Ross A. Crates; Antica Culina; Damien R. Farine; Josh A. Firth; Camilla A. Hinde; Lindall R. Kidd; Nicole D. Milligan; et al. (Behavioral Ecology and Sociobiology, 2015)

Protecting asset value and driving performance with a dynamic, risk-based contingency fund - C. W. Mauelshagen; S. J. T. Pollard; D. Owen; S. Herndlhofer; P. Firth; J. McKenna; N. Bingley; P. Jenson (Environment Systems and Decisions, 2014)

Phylogenetic Analysis Reveals Rapid Evolutionary Dynamics in the Plant RNA Virus Genus Tobamovirus - Israel Pagán; Cadhla Firth; Edward C. Holmes (Journal of Molecular Evolution, 2010)

Novel one-stop multidisciplinary follow-up clinic significantly improves cancer risk management in BRCA1/2 carriers - G. Pichert; C. Jacobs; I. Jacobs; U. Menon; R. Manchanda; M. Johnson; H. Hamed; C. Firth; M. Evison; A. Tutt; L. de Silva; C. Langman; et al. (Familial Cancer, 2010)

Acute whole-body vibration elicits post-activation potentiation - Darryl J. Cochrane; Stephen R. Stannard; Elwyn C. Firth; Jörn Rittweger (European Journal of Applied Physiology, 2010)

Predicting impacts of climate‐induced range expansion: an experimental framework and a test involving key grazers on temperate rocky shores - LOUISE B. FIRTH; TASMAN P. CROWE; PIPPA MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2009)
Climate change has strong potential to modify the structure and functioning of ecosystems, but experimental field studies into its effects are rare. On rocky shores, grazing limpets strongly affect ecosystem structure and their distribution in NW Europe is changing in response to climate change. Three limpet species co‐occur in SW Britain ( Patella vulgata, Patella ulyssiponensis and Patella depressa ) on open rock and in pools. Shores in Ireland are similar, but currently lack P. depressa . It is anticipated that P. depressa will expand its range into Ireland as the climate warms, but we currently lack an empirical basis to predict the consequences of this change. Recent studies show that increasing abundance of P. depressa on British shores has been accompanied by a decline of P. vulgata suggesting interspecific competition. In this study, a new experimental framework was used to examine the potential for P. depressa to affect P. vulgata on Irish shores. P. vulgata was experimentally transplanted into enclosures on open rock and in pools in both Ireland and Britain. In pools, treatments also included transplanted P. ulyssiponensis to mimic natural assemblages. Growth and mortality of P. vulgata were measured over 6 months with no differences between Ireland and Britain. In Britain, P. vulgata caged in pools with transplanted P. depressa and P. ulyssiponensis showed reduced growth, compared with when caged in pools with P. ulyssiponensis alone. There was no effect of P. depressa on the growth rate of P. vulgata on open rock. Results indicate that if the range of P. depressa extends into Ireland, it would reduce the growth of P. vulgata where it co‐occurs with P. ulyssiponensis in pools. The framework used here provides a field‐based approach that could be used to examine the impacts of climate‐induced range expansions on the structure and functioning of other ecosystems.

Environmental relationships of the brush‐tailed rabbit‐rat, Conilurus penicillatus , and other small mammals on the Tiwi Islands, northern Australia - Ronald S. C. Firth; John C. Z. Woinarski; Kym G. Brennan; Craig Hempel (Journal of Biogeography, 2006)
Aim To describe the habitat characteristics and status of the brush‐tailed rabbit‐rat, Conilurus penicillatus Gould, 1842, on the Tiwi Islands, northern Australia, as part of a broader programme aimed at the conservation management of this species. In addition, comparable environmental modelling is undertaken for other co‐occurring small native mammals, including the black‐footed tree‐rat, Mesembriomys gouldii Gray, 1843, a taxonomically and ecologically related species. These objectives relate to the significance for mammal conservation of islands generally in Australia, and the recent intensification of plantation forestry on these previously little‐disturbed islands. Location Melville and Bathurst islands (Tiwi Islands), respectively, Australia's second and fifth largest islands. Methods A systematic survey was conducted for mammals across Bathurst (115 sampled quadrats) and Melville Island (236 quadrats). A broad range of environmental variables was recorded for every quadrat. All quadrats were classified by their woody plant species composition. The relative occurrence of individual mammal species across the resulting vegetation groups was examined using Kruskal–Wallis anova . The habitat relationships of C. penicillatus and the most commonly recorded mammal species were described by generalized linear modelling, with separate models for each island, for both islands combined, for all habitats and for only those sites dominated by eucalypts. Results Twelve small mammal species (excluding bats, macropods and feral animals) were recorded in this study. The most notable feature of this survey was the lack of records of M. gouldii from Bathurst Island. In contrast, the proportion of quadrats with C. penicillatus was not significantly different between the two islands. There was no significant tendency for these two species to co‐occur in quadrats on Melville Island more or less commonly than by chance. Conilurus penicillatus was most abundant in eucalypt forest while M. gouldii showed a weak association with eucalypt forests and woodlands and shrub land. The five most commonly recorded species showed highly idiosyncratic relationships with environmental variables, with this relationship showing some variation between the two islands. None showed any significant association with floristic variation within the extensive eucalypt forests, but most showed significant associations with tree height, basal area (especially of large trees), landscape position (distance to watercourse) and fire history. Main conclusions Conilurus penicillatus was most likely to occur in tall eucalypt forest away from watercourses. This habitat is now being targeted for clearance for the development of plantations of the exotic Acacia mangium . Seven of the 12 mammal species examined in this study ( C. penicillatus , M. gouldii , Rattus tunneyi Thomas, 1904, Melomys burtoni Ramsay, 1887, Sminthopsis butleri Archer, 1979, Phascogale tapoatafa Meyer, 1793 and Petaurus breviceps Gould, 1842) were not recorded at all in plantations, and these (and other) species are likely to be severely disadvantaged by plantation development. The study also demonstrated that the two medium to large arboreal rodent species ( C. penicillatus and M. gouldii ) vary in environmental associations and found no evidence that C. penicillatus increased in areas unoccupied by M. gouldii .